Gangliosides: Treatment Avenues in Neurodegenerative Disease - Magistretti, Pierre J.; Geisler, Fred H.; Schneider, Jay S.; Li, P. Andy; Fiumelli, Hubert; Sipione, Simonetta (Frontiers in Neurology, 2019)
Gangliosides are cell membrane components, most abundantly in the central nervous system where they exert among others neuro-protective and -restorative functions. Clinical development of ganglioside replacement therapy for several neurodegenerative diseases was impeded by the BSE crisis in Europe during the 1990s. Nowadays, gangliosides are produced bovine-free and new pre-clinical and clinical data justify a reevaluation of their therapeutic potential in neurodegenerative diseases. Clinical experience is greatest with monosialo-tetrahexosyl-ganglioside (GM1) in the treatment of stroke. Fourteen randomized controlled trials (RCTs) in overall >2'000 patients revealed no difference in survival, but consistently superior neurological outcomes versus placebo. GM1 was shown to attenuate ischemic neuronal injuries in diabetes patients by suppression of ERK1/2 phosphorylation and reduction of stress to the endoplasmic reticulum. There is level-I evidence from 5 RCTs of a significantly faster recovery with GM1 versus placebo in patients with acute and chronic spinal cord injury (SCI), disturbance of consciousness after subarachnoid hemorrhage, or craniocerebral injuries due to closed head trauma. In Parkinson's disease (PD), two RCTs provided evidence of GM1 to be superior to placebo in improving motor symptoms and long-term to result in a slower than expected symptom progression, suggesting disease-modifying potential. In Alzheimer’s disease (AD), the role of gangliosides has been controversial, with some studies suggesting a “seeding” role for GM1 in amyloid β polymerization into toxic forms, and others more recently suggesting a rather protective role in vivo. In Huntington’s disease (HD), no clinical trials have been conducted yet. However, low GM1 levels observed in HD cells were shown to increase cell susceptibility to apoptosis. Accordingly, treatment with GM1 increased survival of HD cells in vitro and consistently ameliorated pathological phenotypes in several murine HD models, with effects seen at molecular, cellular, and behavioral level. Given that in none of the clinical trials using GM1 any clinically relevant safety issues have occurred to date, current data supports expanding GM1 clinical research, particularly to conditions with high, unmet medical need.